The contribution of the Youth Communication Center (YCC) to the peace building process in the area of Bosnia and Herzegovina and in the region - Kelava Vera (Temida)
Ever since its formation, the YCC has been working intensely on the reconciliation process and peace building. Over the past few years, we have implemented programs and conducted activities aimed at different categories of the population (refugees and displaced persons, ethnic minorities returnees, discharged soldiers, representatives of political parties representatives of local NGO-s, etc) in more than 40 communities in Bosnia and Herzegovina and broader. During our activities, we have developed a methodology of education on reconciliation and peace building by adapting the experiences of the good practice from other countries to the needs of the local environment we work in. In addition, we also organize programs aiming at connecting the young people in the region, actions and campaigns of public advocacy aimed at bringing about democratic change on the local and on the state level, counseling and psychotherapy for the vulnerable groups of citizens, continual media promotion of reconciliation over radio programs, we organize education for local experts dealing with reconciliation issues etc.